Surfactant presence in a multilayer polyelectrolyte-enzyme system improves its catalytic response - Cortez, María Lorena (2009)
Self-assembling of poly(allylamine) containing an osmium polypyridil complex (PAOs) alternatively with sodium dodecyl sulfate (SDS) and glucose oxidase (GOx) generates a ternary multilayer system, (PAOs/SDS/PAOs/GOx)n. The introduction of this anionic surfactant allows a sensitive increase of the polyelectrolyte and the enzyme uptake at pH 7.0, enhancing its catalytic behavior in presence of glucose more than 5 times, compared to the system (PAOs/GOx)n constructed at the same pH. The balance between ionic and hydrophobic interactions in the construction of this system is discussed.